Changing patterns of dividend paying industrial firms on the Johannesburg Stock Exchange - Ramokgopa, Morathi (My University, 2018)
The following study examined whether there are changes in the patterns of dividend paying Industrial firms on the JSE Limited over the 1990 to 2015 period. The patterns were identified by examining three factors based on the findings of Fama and French (2001), and DeAngelo, DeAngelo, and Skinner (2004). Data was collected from the INET BFA database, consisting of 51 industrial firms. These firms were further classified into two groups, namely: dividend payers and non-dividend payers. The non-dividend payers are classified as former payers and firms that have never paid dividends. The first factor examined the relationship between dividend payments and firm characteristics in the form of firm size, profitability, and investment opportunities. Fama and French (2001) found that dividend payers tend to be large, profitable, and did not aggressively pursue investment opportunities. Using summary statistics, this study finds that dividend payers are large in size, relatively more profitable than non-payers, and do not pursue as many investment opportunities, compared to former dividend payers. However, dividend payers are found to have the best growth opportunities when an alternative measure is used for investment opportunities. Unlike the findings of Fama and French (2001) the logistic regression results do not confirm the findings based on the summary statistics. The logistic regression results suggest that profitability is the only firm characteristic that is significant in determining the probability of dividend payouts over the sample period. The regression results are mixed over the identified sub-periods. Furthermore, the multiple linear regression results suggest that size and investment opportunities are the only significant factors in the probability of dividend payouts over the sample period. In addition, the regression results are mixed over the identified sub-periods. The second factor examined whether the propensity to pay dividends has increased or decreased over the period. Fama and French (2001) found that given the firm size, probability, and investment opportunities characteristics, firms have become less likely to pay dividends. This study finds that there is increasing propensity to pay dividends during the sub-periods of 1994 to 2001 and 2010 to 2015. However, there is a decreasing propensity to pay dividends during the 2002 to 2009 sub-period. This study suggests that the macroeconomic events during these sub-periods and advancements on the JSE Limited contribute to the propensity to pay dividends. ii The third factor examined whether the proportion of dividend payers had increased over the period and whether this implied an increase or decrease in dividend and earnings concentration. Fama and French (2001) found that the proportion of firms paying cash dividends decreased over the period, due in part to changing firm characteristics of publicly traded firms in the U.S. This study finds that the number of dividend paying firms on the JSE Limited increases over the period but decreases over the 2006 to 2015 sub-period. From 2006 onwards, the proportion of dividend payers decreases significantly, whilst the proportions of non-payers increases. Unlike Fama and French (2001), new lists do not necessarily seem to contribute to the declining proportion of payers over the period. In addition, DeAngelo et al. (2004) found that aggregate earnings and dividends concentration had increased over the period despite the decline in the proportion of listed publicly listed dividend paying U.S. firms. They specifically found that a smaller proportion of dividend paying firms account for the vast bulk of dividend payments and earnings. This study finds that aggregate dividends and earnings increased over the sample period. Similar to DeAngelo et al. (2004), a relatively small number of firms pay the overwhelming majority of aggregate industrial dividends. However, contrary to DeAngelo et al. (2004) dividend concentration has decreased over the period. The findings of this study therefore suggest that given the changes in the relationship between firm characteristics and the probability of dividend payments and the changing propensity to pay dividends over the sub-periods, dividends are not disappearing. Therefore, the changing patterns of dividend paying firms have not resulted in a disappearance of dividends over the 1990 to 2015 period. A few recommendations are proposed post the findings of the study. The first recommendation is to consider a wider set of firm characteristics in addition to the characteristics identified by Fama and French (2001). A second recommendation is to consider specific macro-economic variables, such as indicators for GDP, foreign exchange investment, Consumer Price Inflation (CPI), Producer Price Inflation (PPI), and share prices. The third recommendation is to consider the capital structure decisions that affect dividend payments, such as debt facilities that may restrict dividend payments. A final recommendation is to consider tax variables, such as the corporate and the dividend withholding taxes, in relation to dividend decisions.
A research report submitted to the Faculty of Commerce, Law and Management, in partial fulfilment of the requirements for the degree of Master of Commerce in Finance, University of the Witwatersrand, Johannesburg, 2018
Keywords: Dividends--South Africa; Dividends--Taxation--South Africa